Microglial phenotypes in the brains of aging people with Down syndrome and Alzheimer disease: Molecular and cell biology/neuroinflammation. (7th December 2020) - Martini, Alessandra Cadete; Helman, Alex M.; McCarty, Katie; Lott, Ira T.; Doran, Eric; Schmitt, Frederick A.; Head, Elizabeth
Abstract: Background: Microglial cells play an important role in maintaining normal brain function, but changes in microglia morphology may reflect the functional state of the cell, and potentially contribute to the development and progression of Alzheimer disease (AD). People with Down syndrome (DS) inevitably develop AD neuropathology by 40 years of age, but little is known about microglial phenotypes in this population. Methods: Autopsy tissue from the posterior cingulate cortex (PCC) from six groups were included in the study: DS (<40 years), DS with AD (>40 years), sporadic non‐DS AD and young, middle‐aged and aged non‐DS controls. Sections were stained with the microglia marker Iba1 and scanned with the Aperio ScanScope XT digital slide scanner Five microglia morphological types were assessed: ramified, hypertrophic, dystrophic, rod‐shaped and amoeboid. Results: Across all groups, individuals with DS have higher numbers of hypertrophic microglial cells in their white matter. In the gray matter, the numbers of ramified microglial cells declines with age across controls and individuals with DS. Individuals with DSAD had significantly fewer ramified microglia than controls and the younger individuals with DS. Higher numbers of dystrophic microglia were also observed in individuals with DSAD relative to the other groups. Interestingly, individuals with DSAD also exhibited more rod‐shaped and amoeboid cells than the AD group. Conclusion: Overall, individuals with DS and DSAD are associated with a microglial phenotype that distinguishes them from non‐DS controls. Our findings suggest a progressive change in microglia patterns over time as people with DS are aging with a trend towards more dystrophic microglial cells. These results reinforce the differences observed in the neuroinflammation phenotype in individuals with DS, and contribute to our understanding of the role that microglia cells play in the development and progression of AD neuropathology and dementia in people with DS.